Endobronchial ultrasound-guided transbronchial fine needle aspiration: Determinants of adequacy - Ece, Dilek; Hallaç Keser, Sevinç; Ça?layan, Benan; Salepçı, Banu Musaffa; Babür Güler, Gamze; Şensu, Sibel; Geçmen, Gonca Gül; Çoban Kökten, Şermin (Bayçınar Medical Publishing, 2018)
Background: This study aims to evaluate the factors influencing the adequacy of endobronchial ultrasound-guided transbronchial fine needle aspiration specimens. Methods: A retrospective analysis of 1,700 endobronchial ultrasound-guided transbronchial fine needle aspiration samples obtained from 822 patients (500 males, 322 females; mean age 56 +/- 13 years; range 16 to 83 years) was performed between March 2011 and March 2014 at our center. Variables potentially associated with sampling adequacy, such as all cytological materials and procedure notes (lymph node and/or lesion size, localization, needle pass number, and slide number) were examined. Results: The overall specimen adequacy was 79.8%. The specimen adequacy was associated with needle pass number (P <= 0.001). Adequacy rate was 66.9% for one needle pass and 85.8% for three needle passes. According to the sampling regions, adequacy rates showed a difference [69.2%-85.8%; (p <= 0.005)]. In the multivariate logistic regression analysis of subcarinal (7) lymph node station, patient age (odds ratio, 0.983; 95% confidence interval, 0.966-1.000; p=0.049) and number of slides (odds ratio, 1.240; 95% confidence interval, 1.062-1.448; p=0.006) were independent determining factors of specimen adequacy. While independent determinants of specimen adequacy for the right paratracheal (4R) region were lymph node size (odds ratio, 1.486; 95% confidence interval, 0.973-2.268; p=0.067) and number of slides (odds ratio, 1.418; 95% confidence interval, 1.146-1.756; p=0.001), they were lymph node size (odds ratio, 1.594; 95% confidence interval, 0.960-2.645; p=0.071) and number of needle passes (odds ratio, 2.277; 95% confidence interval, 1.360-3.811; p=0.002) for the right interlobar (11R) region. Independent determinant of specimen adequacy for the left paratracheal (4L) lymph node station was the number of needle passes (odds ratio, 1.656; 95% confidence interval, 0.955-2.869; p=0.072). Conclusion: During endobronchial ultrasound-guided transbronchial fine needle aspirations, particularly when rapid on site evaluation cannot be applied, consideration of factors affecting adequacy according to lymph node localizations may increase the chance for obtaining materials with suitable quality for cytologic evaluation.

Amaç: Bu çalışmada endobronşiyal ultrasonografi eşliğinde transbronşiyalince iğne aspirasyonu örneklerinde yeterliliği etkileyen faktörlerdeğerlendirildi.Çalışma planı: Merkezimizde Mart 2011 - Mart 2014 tarihleri arasında822 hastadan (500 erkek, 322 kadın; ort. yaş 56±13 yıl; dağılım 16-83 yıl)edinilen 1700 endobronşiyal ultrasonografi eşliğinde transbronşiyal inceiğne aspirasyonu örneği retrospektif olarak analiz edildi. Tüm sitolojikmateryaller ve işlem notları (lenf nodu veya lezyon boyutu, yerleşim yeri,iğne girişimi sayısı ve yayma preparat sayısı) gibi örnek yeterliliği ile ilişkiliolabilecek değişkenler incelendi.Bulgular: Genel örnek yeterliliği %79.8 idi. Örnek yeterliliği iğne girişimisayısı ile ilişkili idi (p?0.001). Yeterlilik oranı tek iğne girişimi için%66.9, üç iğne girişimi için %85.8 idi. Yeterlilik oranları örneklem almabölgelerine göre farklılık gösterdi [%69.2-%85.8; (p?0.005)]. Subkarinal(7) lenf nodu istasyonunun çok değişkenli lojistik regresyon analizinde,hasta yaşı (göreceli risk oranı, 0.983; %95 güven aralığı, 0.966-1.000;p=0.049) ve yayma preparat sayısı (göreceli risk oranı, 1.240; %95 güvenaralığı, 1.062-1.448; p=0.006) örnek yeterliliğinin bağımsız belirleyicifaktörleri idi. Sağ paratrakeal (4R) bölge için örnek yeterliliğinin bağımsızbelirleyici faktörleri lenf nodu boyutu (göreceli risk oranı, 1.486; %95güven aralığı, 0.973-2.268; p=0.067) ve yayma preparat sayısı (göreceli riskoranı, 1.418; %95 güven aralığı, 1.146-1.756; p=0.001) iken sağ interlober(11R) bölge için lenf nodu boyutu (göreceli risk oranı, 1.594; %95 güvenaralığı, 0.960-2.645; p=0.071) ve iğne girişimi sayısı (göreceli risk oranı,2.277; %95 güven aralığı, 1.360-3.811; p=0.002) idi. Sol paratrakeal (4L)lenf nodu istasyonu için örnek yeterliliğinin bağımsız belirleyici faktörüiğne girişimi sayısı (göreceli risk oranı, 1.656; %95 güven aralığı, 0.955-2.869; p=0.072) idi.Sonuç: Endobronşiyal ultrasonografi eşliğinde transbronşiyal ince iğneaspirasyonlarında, özellikle yerinde hızlı değerlendirme yapılamadığında,lenf nodu yerleşim yerlerine göre yeterliliği etkileyen faktörlerin göz önüne alınması sitolojik değerlendirme için uygun nitelikte materyaller elde edilmesi şansını artırabilir.
Endobronşiyal ultrasonografi eşliğinde transbronşiyal ince iğne aspirasyonu: Yeterliliğin belirleyicileri
WOS: 000438747600018
Keywords: Adequacy; Endobronchial Ultrasound; Transbronchial Fine Needle Aspiration; Yeterlilik; Endobronşiyal Ultrasonografi; Transbronşiyal İnce İğne Aspirasyonu